PEMANFAATAN MEDIA SOSIAL DALAM PENYAMPAIAN ASPIRASI MAHASISWA - Linda Astuti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
This study aims to examine the use of social media in the delivery of student aspiration. Using a qualitative approach to the data collection techniques performed with primary data obtained by direct observation and the observation depth interviews with informants. While it is used with the photo documentation of secondary data field notes, journals, papers, and articles online. Data analysis techniques used to gather research data that is complete, reducing the data to focus on research, data presentation and conclusion. the results are confirmed the validity of the data by using the technique of triangulation. Informants were students who use social media Facebook Ilmu komunikasi Unras for give aspirations. The results showed tlat the use of social media in the delivery of student aspirations through'a Facebook Ilmu komunikasi Unras is also a concern of students and student participation to provide a solution to the problems faced by students. Meanwhile, based on thetheory of Cyber Community mown that the formation community Facebook Ilmu komunikasi Unras due to the same status as a student member ilmu komunikasi unras and becomes a means of delivering the aspirations of students.